2017
DOI: 10.1080/20008198.2017.1321357
|View full text |Cite|
|
Sign up to set email alerts
|

The assessment of psychopathology among traumatized refugees: measurement invariance of the Harvard Trauma Questionnaire and the Hopkins Symptom Checklist-25 across five linguistic groups

Abstract: Background: Questionnaires are widely used to assess the mental health status of refugees, whereas their construct validity largely remains unexplored. Objective: This study examined the construct validity of two widely-used instruments for the assessment of PTSD symptoms (Harvard Trauma Questionnaire [HTQ]; 16 items) and symptoms of anxiety and depression (Hopkins Symptom Check list-25 [HSCL-25]; 25 items) among Dutch and refugee patients with different linguistic backgrounds. Method: We applied exploratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 50 publications
(72 reference statements)
0
65
0
Order By: Relevance
“…The Arabic version of the HTQ was previously used with Iraqi refugees (Shoeb et al., ), and was the basis for this study, with minor adjustments made for the context of the Syrian crisis. We used the first 16 trauma‐symptom items in the HTQ to assess PTSD symptom severity, as these items have been used with other refugees from different non‐Western linguistic populations (Fouchier et al., ; Ichikawa, Nakahara, & Wakai, ; Lhewa, Banu, Rosenfeld, & Keller, ; Wind, van der Aa, de la Rie, & Knipscheer, ). The HTQ total score is an average score, based on a range of responses from 1 ( not at all ) to 4 ( extremely ), with higher scores indicating an ascending level of PTSD symptom severity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arabic version of the HTQ was previously used with Iraqi refugees (Shoeb et al., ), and was the basis for this study, with minor adjustments made for the context of the Syrian crisis. We used the first 16 trauma‐symptom items in the HTQ to assess PTSD symptom severity, as these items have been used with other refugees from different non‐Western linguistic populations (Fouchier et al., ; Ichikawa, Nakahara, & Wakai, ; Lhewa, Banu, Rosenfeld, & Keller, ; Wind, van der Aa, de la Rie, & Knipscheer, ). The HTQ total score is an average score, based on a range of responses from 1 ( not at all ) to 4 ( extremely ), with higher scores indicating an ascending level of PTSD symptom severity.…”
Section: Methodsmentioning
confidence: 99%
“…The HTQ total score is an average score, based on a range of responses from 1 ( not at all ) to 4 ( extremely ), with higher scores indicating an ascending level of PTSD symptom severity. Though there has been some dispute regarding the use of HTQ cutoff scores with different cultural groups (Rasmussen, Verkuilen, Ho, & Fan, ), a recent investigation of the factor structure and measurement invariance of the HTQ found that “…meaningful comparisons of observed PTSD scale scores on the HTQ between refugee patients with different non‐Western linguistic backgrounds can be made” (Wind et al., , p. 8). Reliability of the 16‐item HTQ in this study was Cronbach's α = .89.…”
Section: Methodsmentioning
confidence: 99%
“…From the HSCL-25, only the depression items (item 11-25) were used. HTQ and HSCL-25 are valid questionnaires to assess symptoms of PTSD, depression, and anxiety in trauma-affected refugees (Wind, van der Aa, de la Rie, & Knipscheer, 2017). All questionnaires were available in the participants' native language, and translators were accessible throughout the study.…”
Section: Clinical Assessmentsmentioning
confidence: 99%
“…The HTQ is a suitable screening tool for PTSD, with a cut-off score of 2.5 (e.g., Mollica et al 1992), based on the first 16 items of part 3, as an established cut-off for the DSM-IV PTSD diagnosis (Wind et al 2017). The instrument has proven to be valid and reliable (Mollica et al 2004).…”
Section: Methodsmentioning
confidence: 99%